Aluminum plastic film with smooth surface and corrosion resistance and preparation method thereof
By passing the aluminum foil and layer composite, and smooth and anti-corrosion treatment of the aluminum plastic film, forming a composite structure and anti-corrosion smooth layer, the problems of surface astringent and poor punch resistance during the depth process of aluminum plastic film are solved, and better depth and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411599642.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-25
AI Technical Summary
The existing aluminum-plastic film has astringent surface during the depth process, poor punch resistance, and the slip agent with corrosion-resistant coating is easy to migrate at high temperatures, affecting the performance of the material.
By passing the aluminum foil and layer composite operation, a composite structure of the passivation aluminum foil and nylon and CPP layers is formed, and the semi-finished aluminum-plastic film is subjected to smooth and anti-corrosion treatment and gradient curing operations to form an anti-corrosion sliding layer and a sliding layer to improve the depth performance and corrosion resistance of the material.
It significantly improves the depth performance of aluminum-plastic film and corrosion resistance of the outer surface, avoids the problems of astringent surface and excessive smoothness, and ensures the safety of the battery.
Smart Images

Figure CN119505615A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of packaging materials, in particular to an aluminum-plastic film with a smooth surface and corrosion resistance and a preparation method thereof. Background Art
[0002] In recent years, soft-package lithium-ion batteries have become a widely used rechargeable battery, mainly used in electric vehicles, hybrid electric vehicles, personal computers, cameras and mobile phones. Compared with the traditional metal shell welding and sealing of batteries, soft-package lithium-ion batteries use aluminum-plastic film as the outer packaging material of the battery core. They have the advantages of high energy density, easy processing into various shapes, and can achieve thinness and lightness. The general aluminum-plastic film includes PET, nylon, aluminum layer and CPP layer arranged in sequence from the outside to the inside. The PET on the aluminum-plastic film is thin and has poor anti-punching ability, which greatly reduces the anti-punching ability of the aluminum-plastic film. If PET is discarded, during the preparation of soft-pack lithium batteries, when the electrolyte is injected, the electrolyte often drips onto the surface of the aluminum-plastic composite film, thereby contaminating the outer surface of the nylon film. For example, in the Chinese invention patent with application number 202310949149.3, a corrosion-resistant coating is formed on the nylon layer to ensure the corrosion resistance of the outer surface of the aluminum-plastic film. However, since the layer structure of the aluminum-plastic film needs to undergo multiple Compounding and high-temperature aging, and multiple high-temperature aging make the surface of the aluminum-plastic film product astringent, resulting in poor deep-punching performance and unable to meet the needs of users. For example, in the Chinese invention patent application with application number 202211571117.6, a lubricant is added to the corrosion-resistant coating formed on the nylon surface, but the lubricant erucamide and oleamide are easy to migrate at high temperatures and cause the surface to become astringent, affecting the smooth effect of the surface of the nylon material layer, resulting in poor deep-punching performance, and powder falling off during the shell punching process, which pollutes the user's mold and causes bumps on the battery appearance, affecting the appearance and unable to meet the needs of users. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an aluminum-plastic film having a smooth surface and corrosion resistance and a preparation method thereof, which can improve the aluminum-plastic film's deep-drawing performance and outer surface corrosion resistance, thereby better meeting the needs of users.
[0004] The objective of the present invention is achieved through the following technical solutions:
[0005] A method for preparing a smooth and corrosion-resistant aluminum-plastic film comprises the following steps:
[0006] Performing a surface passivation treatment operation on the aluminum foil to obtain a passivated aluminum foil;
[0007] Performing a layer compounding operation on the passivated aluminum foil so that the matte surface of the passivated aluminum foil is compounded with the nylon material layer, and the bright surface of the passivated aluminum foil is compounded with the CPP layer, to obtain a composite aluminum foil;
[0008] Performing a aging operation on the composite aluminum foil to obtain a semi-finished aluminum-plastic film;
[0009] Performing a lubrication and anti-corrosion treatment on the semi-finished aluminum-plastic film so as to form an anti-corrosion and lubrication layer on the surface of the nylon material layer of the semi-finished aluminum-plastic film;
[0010] The pre-treated aluminum-plastic film is subjected to a slippery treatment so that a slippery layer is formed on the surface of the CPP layer of the semi-finished aluminum-plastic film.
[0011] In one embodiment, the semi-finished aluminum-plastic film is treated with an anti-corrosion and anti-slip coating;
[0012] The anti-corrosion and slippery coating comprises the following components in parts by weight:
[0013]
[0014] The main agent at least includes organosilicon-modified acrylate and chemical corrosion-resistant fluoropolymer.
[0015] In one embodiment, the chemically resistant fluoropolymer is at least one of polytetrafluoroethylene (PTFE), fluorinated ethylene propylene (FEVAC), fluorinated alkyl acrylate (FMA) and fluorinated ethylene propylene copolymer (FEP).
[0016] In one of the embodiments, the mass ratio of the organosilicon-modified acrylate to the chemically-resistant fluoropolymer is (0.5-2):1.
[0017] In one of the embodiments, the mass percentage concentration of the organosilicon-modified acrylate in the anti-corrosion and slippery coating is 15% to 30%.
[0018] In one embodiment, the method for preparing the anti-corrosion and slippery coating comprises the following steps:
[0019] The silicone-modified acrylate and the chemical corrosion-resistant fluoropolymer are mixed to obtain the main agent;
[0020] Adding a solvent to the main agent to perform a first stirring and mixing operation to obtain a first mixed solution;
[0021] Adding the epoxy curing agent to the first mixed liquid to perform a second stirring and mixing operation to obtain a second mixed liquid;
[0022] The isocyanate curing agent is added to the second mixed liquid to perform a third stirring and mixing operation to obtain the anti-corrosion and slippery coating.
[0023] In one embodiment, the epoxy curing agent is added to the first mixed liquid for a second stirring and mixing operation, with a stirring speed of 350±50 r / min and a stirring time of 4 min to 8 min.
[0024] In one embodiment, the isocyanate curing agent is added to the second mixed liquid for a third stirring and mixing operation, with a stirring speed of 350±50 r / min and a stirring time of 8 min to 12 min.
[0025] In one embodiment, before the step of performing a smooth treatment on the pretreated aluminum-plastic film and after the step of performing a smooth and anti-corrosion treatment on the semi-finished aluminum-plastic film, the method for preparing the aluminum-plastic film with a smooth and corrosion-resistant surface further comprises the following steps:
[0026] The semi-finished aluminum-plastic film after the lubrication and anti-corrosion treatment is subjected to a gradient curing operation, so that an anti-corrosion and lubrication layer is formed on the surface of the nylon material layer of the semi-finished aluminum-plastic film.
[0027] In one embodiment, before the step of performing a smooth and anti-corrosion treatment on the semi-finished aluminum-plastic film and after the step of performing a aging operation on the composite aluminum foil, the method for preparing the aluminum-plastic film with a smooth surface and corrosion resistance further includes the following step: performing a corona treatment on the nylon material layer of the semi-finished aluminum-plastic film.
[0028] A corrosion-resistant aluminum-plastic film with a smooth surface is prepared by the method for preparing the corrosion-resistant aluminum-plastic film with a smooth surface described in any of the above embodiments.
[0029] Compared with the prior art, the present invention has at least the following advantages:
[0030] The method for preparing the aluminum-plastic film with a smooth and corrosion-resistant surface comprises the following steps: firstly, performing a surface passivation treatment operation on the aluminum foil, and then performing a layer composite operation on the passivated aluminum foil, so as to better realize the composite of the nylon material layer and the CPP layer on the passivated aluminum foil; then performing a aging operation on the composite aluminum foil, so as to better ensure the composite strength of the nylon material layer and the CPP layer on the passivated aluminum foil; finally, performing a smooth and corrosion-resistant treatment on the semi-finished aluminum-plastic film, and performing a smooth treatment on the pre-treated aluminum-plastic film, so as to directly reduce the stamping friction; and the anti-corrosion smooth layer is used to compensate for and buffer the stamping friction, so that the smooth performance of the smooth layer can better ensure the deep punching performance and the outer surface corrosion resistance of the aluminum-plastic film without affecting the packaging bonding strength, thereby better meeting the needs of users, avoiding the problem that the smooth effect of the smooth layer formed on the surface of the CPP layer of the aluminum-plastic film is too strong, that is, avoiding the problem that the surface of the CPP layer of the aluminum-plastic film is too smooth, thereby affecting the packaging bonding strength of the aluminum-plastic film, and better ensuring the use safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 The present invention is a flowchart of a method for preparing a smooth and corrosion-resistant aluminum-plastic film according to an embodiment of the present invention;
[0033] Figure 2 This is the aluminum-plastic film prepared in Example 15-6 of the present invention. DETAILED DESCRIPTION
[0034] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0035] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0037] The present application provides a method for preparing an aluminum-plastic film with a smooth surface and corrosion resistance. The above-mentioned method for preparing an aluminum-plastic film with a smooth surface and corrosion resistance comprises the following steps: performing a surface passivation treatment operation on an aluminum foil to obtain a passivated aluminum foil; performing a layer composite operation on the passivated aluminum foil to composite the matte surface of the passivated aluminum foil with a nylon material layer, and the bright surface of the passivated aluminum foil with a CPP layer to obtain a composite aluminum foil; performing a aging operation on the composite aluminum foil to obtain a semi-finished aluminum-plastic film; performing a smooth and anti-corrosion treatment on the semi-finished aluminum-plastic film to form an anti-corrosion and smooth layer on the surface of the nylon material layer of the semi-finished aluminum-plastic film; performing a smooth treatment on the pretreated aluminum-plastic film to form a smooth layer on the surface of the CPP layer of the semi-finished aluminum-plastic film.
[0038] The method for preparing the aluminum-plastic film with a smooth and corrosion-resistant surface comprises the following steps: firstly, the aluminum foil is subjected to a surface passivation treatment operation, and then the passivated aluminum foil is subjected to a layer composite operation, so as to better realize the composite of the nylon material layer and the CPP layer on the passivated aluminum foil; then, the composite aluminum foil is subjected to a aging operation, so as to better ensure the composite strength of the nylon material layer and the CPP layer on the passivated aluminum foil; finally, the semi-finished aluminum-plastic film is subjected to a smooth and anti-corrosion treatment, and then the pre-treated aluminum-plastic film is subjected to a smooth treatment, so as to directly reduce the stamping friction; and the anti-corrosion smooth layer is used to compensate for and buffer the stamping friction, so that the smooth performance of the smooth layer can better ensure the deep punching performance and the outer surface corrosion resistance of the aluminum-plastic film without affecting the packaging bonding strength, thereby better meeting the needs of users, avoiding the problem that the smooth effect of the smooth layer formed on the surface of the CPP layer of the aluminum-plastic film is too strong, that is, avoiding the problem that the surface of the CPP layer of the aluminum-plastic film is too smooth, thereby affecting the packaging bonding strength of the aluminum-plastic film, and better ensuring the safety of battery use.
[0039] It should be noted that when the lubricant is directly added to the nylon material layer or the CPP layer, the lubricating effect of the lubricant will reduce the bonding strength of the nylon material layer or the CPP layer, that is, it will affect the bonding strength of the layers of the aluminum-plastic film, and then affect the peel strength of the aluminum-plastic film, and affect the safety of use of the aluminum-plastic film. Therefore, in the present application, an anti-corrosion lubricant layer and a lubricant layer are respectively formed on the surface of the nylon material layer or the CPP layer, so that the peel strength of the aluminum-plastic film is ensured, and the punching performance and outer surface corrosion resistance of the aluminum-plastic film are better ensured, thereby better meeting the needs of users.
[0040] In order to better understand the method for preparing the aluminum-plastic film with a smooth surface and corrosion resistance of the present application, the method for preparing the aluminum-plastic film with a smooth surface and corrosion resistance of the present application is further explained below:
[0041] See also Figure 1 , a method for preparing a smooth and corrosion-resistant aluminum-plastic film in one embodiment comprises the following steps:
[0042] S100, performing a surface passivation treatment operation on the aluminum foil to obtain a passivated aluminum foil, which is beneficial to the passivated aluminum foil being respectively composited with the nylon material and the CPP layer, and is beneficial to improving the corrosion resistance of the passivated aluminum foil.
[0043] S200, performing a layer-compounding operation on the passivated aluminum foil, so that the matte surface of the passivated aluminum foil is compounded with the nylon material layer, and the bright surface of the passivated aluminum foil is compounded with the CPP layer, to obtain a composite aluminum foil, which better ensures the corrosion resistance and structural strength of the aluminum-plastic film.
[0044] S300, performing a aging operation on the composite aluminum foil to obtain a semi-finished aluminum-plastic film, thereby better ensuring the stable compounding of the aluminum foil, nylon material and CPP layer in the aluminum-plastic film.
[0045] S400, performing a lubrication and anti-corrosion treatment on the semi-finished aluminum-plastic film, so that an anti-corrosion and lubrication layer is formed on the surface of the nylon material layer of the semi-finished aluminum-plastic film, so that the outer surface of the nylon material layer has lubricity and corrosion resistance, and the lubrication and corrosion resistance of the aluminum-plastic film are initially improved, thereby effectively reducing the corrosion of the nylon material layer during the liquid injection process, thereby effectively ensuring the safety of the battery.
[0046] S500, performing a lubricity treatment on the pre-treated aluminum-plastic film, so that a lubricity layer is formed on the surface of the CPP layer of the semi-finished aluminum-plastic film. It can be understood that, since the contact surface for direct stamping of the aluminum-plastic film is the CPP layer, only the anti-corrosion and smooth layer is formed on the nylon layer of the aluminum-plastic film, and the actual smooth effect on the aluminum-plastic film is poor, that is, it actually indirectly reduces the stamping friction, which makes the anti-deep impact performance of the aluminum-plastic film still unable to meet the needs of users. Thus, in the present application, on the basis of forming the anti-corrosion and smooth layer on the surface of the nylon material layer of the aluminum-plastic film, the surface of the CPP layer of the aluminum-plastic film is further formed with a smooth layer, so that the stamping friction is directly reduced, and the anti-corrosion and smooth layer is cooperated to compensate for the buffering stamping friction, so that the smooth performance of the smooth layer can better ensure the deep impact performance and the corrosion resistance of the outer surface of the aluminum-plastic film without affecting the packaging bonding strength, thereby better meeting the needs of users, avoiding the problem of too strong smooth effect of the smooth layer formed on the surface of the CPP layer of the aluminum-plastic film, that is, avoiding the excessive smoothness of the surface of the CPP layer of the aluminum-plastic film, thereby affecting the packaging bonding strength of the aluminum-plastic film, and better ensuring the safety of battery use.
[0047] The method for preparing the aluminum-plastic film with a smooth and corrosion-resistant surface comprises the following steps: firstly, the aluminum foil is subjected to a surface passivation treatment operation, and then the passivated aluminum foil is subjected to a layer composite operation, so as to better realize the composite of the nylon material layer and the CPP layer on the passivated aluminum foil; then, the composite aluminum foil is subjected to a aging operation, so as to better ensure the composite strength of the nylon material layer and the CPP layer on the passivated aluminum foil; finally, the semi-finished aluminum-plastic film is subjected to a smooth and anti-corrosion treatment, and then the pre-treated aluminum-plastic film is subjected to a smooth treatment, so as to directly reduce the stamping friction; and the anti-corrosion smooth layer is used to compensate for and buffer the stamping friction, so that the smooth performance of the smooth layer can better ensure the deep punching performance and the outer surface corrosion resistance of the aluminum-plastic film without affecting the packaging bonding strength, so as to better meet the needs of users, avoid the problem that the smooth effect of the smooth layer formed on the surface of the CPP layer of the aluminum-plastic film is too strong, that is, avoid the excessive smoothness of the surface of the CPP layer of the aluminum-plastic film, and then affect the packaging bonding strength of the aluminum-plastic film, and better ensure the safety of battery use.
[0048] In one embodiment, the aluminum foil is subjected to a surface passivation treatment operation, specifically: the aluminum foil is subjected to trivalent chromium passivation. It can be understood that trivalent chromium passivation of aluminum foil is an environmentally friendly and efficient surface treatment technology, which is a relatively mature technology and will not be described in detail here. It is mainly used to improve the corrosion resistance of the aluminum foil and extend its service life so that the surface of the aluminum foil has better adhesion. Furthermore, the thickness of the aluminum foil is 35μm to 55μm.
[0049] In one embodiment, a polyurethane adhesive is used to compound the matte surface of the passivated aluminum foil and the nylon material layer. Further, the thickness of the nylon is 15μm to 30μm. In one embodiment, a modified polyolefin adhesive is used to compound the bright surface of the passivated aluminum foil and the CPP layer. Further, the thickness of the CPP layer is 35μm to 80μm. It can be understood that the compounding is the adhesive compounding of the two-layer structure, and the layer structure of the adhesive compound is further subjected to high-temperature aging, that is, the adhesive fixed connection of the layer structure is completed. Further, the modified polyolefin adhesive is a maleic anhydride modified polypropylene adhesive.
[0050] In one embodiment, the composite aluminum foil is subjected to a gradient aging operation so that the composite aluminum foil is aging at a gradient temperature. Further, the composite aluminum foil is subjected to a gradient aging operation, specifically including the following steps: placing it at room temperature for 1 hour to 10 hours to allow the glue to fully penetrate into each film layer; then, placing it at a temperature of 40°C to 45°C for 12 hours to 24 hours to allow the glue to flow better; finally, placing it at a temperature of 50°C to 70°C for 96 hours to 168 hours to allow the glue to fully solidify.
[0051] In one of the embodiments, the semi-finished aluminum-plastic film is treated with an anti-corrosion and slippery coating; wherein the anti-corrosion and slippery coating comprises the following components by mass: 75 to 85 parts of the main agent; 10 to 15 parts of the epoxy curing agent; 5 to 10 parts of the isocyanate curing agent; the solvent balance; the main agent at least comprises silicone-modified acrylate and anti-chemical corrosion fluoropolymer. It can be understood that the epoxy resin curing agent promotes the curing of epoxy resin and improves the mechanical properties and durability of the material; the isocyanate curing agent can accelerate the curing speed of the main agent, reduce the aging time, and improve the production efficiency. The main agent at least comprises silicone-modified acrylate and anti-chemical corrosion fluoropolymer, so that the formed anti-corrosion and slippery layer and the nylon material layer have good adsorption, thermal stability and chemical stability, and are corrosion-resistant, have high mechanical strength, are not easy to fall off and have good slippery effect, and are resistant to high and low temperatures of 50°C to 120°C.
[0052] In one embodiment, the chemically resistant fluoropolymer is at least one of polytetrafluoroethylene (PTFE), fluorinated ethylene propylene (FEVAC), fluorinated alkyl acrylate (FMA) and fluorinated ethylene propylene copolymer (FEP).
[0053] In one embodiment, the mass ratio of the organosilicon-modified acrylate to the chemically-resistant fluoropolymer is (0.5-2): 1. Furthermore, the mass ratio of the organosilicon-modified acrylate to the chemically-resistant fluoropolymer is 1:1.
[0054] In one embodiment, the mass percentage concentration of the organosilicon-modified acrylate in the anti-corrosion and slippery coating is 15% to 30%.
[0055] In one embodiment, the solvent of the anti-corrosion and slippery coating includes cyclohexane and ethyl acetate. Further, the volume ratio of cyclohexane and ethyl acetate in the solvent is (3-5):1.
[0056] In one embodiment, the epoxy curing agent is diethylenetriamine or triethylenetetramine.
[0057] In one embodiment, the isocyanate curing agent is hexamethylene diisocyanate trimer or diphenylmethane diisocyanate.
[0058] In one embodiment, the method for preparing the anti-corrosion and slippery coating comprises the following steps:
[0059] The silicone-modified acrylate and the chemical corrosion-resistant fluoropolymer are mixed to obtain a main agent;
[0060] Adding a solvent to the main agent to perform a first stirring and mixing operation to obtain a first mixed solution;
[0061] Adding epoxy curing agent to the first mixed liquid to perform a second stirring and mixing operation to obtain a second mixed liquid;
[0062] Add isocyanate curing agent to the second mixed liquid and perform a third stirring and mixing operation to obtain an anti-corrosion and smooth coating.
[0063] It is understandable that the NCO group in the isocyanate curing agent reacts with the OH group in the epoxy resin, and the mixed curing agent may gel quickly and become unusable, or the curing effect may be unsatisfactory. Therefore, it is recommended to use the isocyanate curing agent in conjunction with the epoxy curing agent to reduce the amount of isocyanate curing agent used, and finally add and stir the epoxy curing agent after mixing with the main agent, thereby better ensuring the curing effect and efficiency of the main agent.
[0064] In one embodiment, the organosilicon-modified acrylate and the chemically-resistant fluoropolymer are mixed until the organosilicon-modified acrylate and the chemically-resistant fluoropolymer are fully mixed. Further, the organosilicon-modified acrylate and the chemically-resistant fluoropolymer are mixed and stirred at a stirring speed of 250±50 r / min for a stirring time of more than 10 min.
[0065] In one embodiment, a solvent is added to the main agent to perform a first stirring and mixing operation, with a stirring speed of 250±50 r / min and a stirring time of 8 min to 15 min.
[0066] In one embodiment, epoxy curing agent is added to the first mixed liquid for a second stirring and mixing operation, with a stirring speed of 350±50 r / min and a stirring time of 4 min to 8 min.
[0067] In one embodiment, isocyanate curing agent is added to the second mixed liquid for a third stirring and mixing operation, with a stirring speed of 350±50 r / min and a stirring time of 8 min to 12 min.
[0068] In one embodiment, the semi-finished aluminum-plastic film is treated with an anti-corrosion and lubricating coating, specifically, the anti-corrosion and lubricating coating is sprayed on the surface of the nylon material layer of the semi-finished aluminum-plastic film. Further, the anti-corrosion and lubricating coating is transported to a pulse-type release electromagnetic nozzle by pressurization, and then the anti-corrosion and lubricating coating is evenly sprayed on the surface of the nylon material layer of the semi-finished aluminum-plastic film by the pulse-type release electromagnetic nozzle.
[0069] In one embodiment, before the step of performing a smooth and anti-corrosion treatment on the semi-finished aluminum-plastic film and after the step of performing a aging operation on the composite aluminum foil, the method for preparing a smooth and anti-corrosion aluminum-plastic film further includes the following steps: performing a corona treatment on the nylon material layer of the semi-finished aluminum-plastic film. Further, the nylon material layer of the semi-finished aluminum-plastic film is subjected to a corona treatment using a corona machine with a power of 0.5 to 1.5 Kw, which improves the adhesion of the surface of the nylon material layer, thereby improving the adhesion strength of the anti-corrosion and smooth layer to the nylon material layer.
[0070] In one embodiment, before the step of performing a lubricity treatment on the pretreated aluminum-plastic film and after the step of performing a lubricity and anti-corrosion treatment on the semi-finished aluminum-plastic film, the method for preparing an aluminum-plastic film with a smooth and corrosion-resistant surface also includes the following step: performing a gradient curing operation on the semi-finished aluminum-plastic film after the lubricity and anti-corrosion treatment to form an anti-corrosion and lubricity layer on the surface of the nylon material layer of the semi-finished aluminum-plastic film.
[0071] In one embodiment, the semi-finished aluminum-plastic film after the slippery and anti-corrosion treatment is subjected to a gradient curing operation, which specifically includes the following steps:
[0072] Perform transition curing treatment on semi-finished aluminum-plastic film;
[0073] Performing constant speed curing treatment on the semi-finished aluminum-plastic film after transition curing treatment;
[0074] The semi-finished aluminum-plastic film after constant-speed curing is subjected to reduced-speed curing.
[0075] In one embodiment, the semi-finished aluminum-plastic film is subjected to transition curing treatment at a temperature of 55°C to 90°C. Further, the semi-finished aluminum-plastic film is subjected to transition curing treatment, specifically: the semi-finished aluminum-plastic film is cured at a temperature of 55°C to 75°C, and then the semi-finished aluminum-plastic film is cured at a temperature of 70°C to 90°C. Further, the semi-finished aluminum-plastic film is cured at a temperature of 55°C to 75°C for 5s to 8s. Further, the semi-finished aluminum-plastic film is cured at a temperature of 70°C to 90°C for 5s to 8s.
[0076] In one embodiment, the semi-finished aluminum-plastic film after the transition curing treatment is subjected to constant-speed curing treatment at a temperature of 100° C. to 120° C. Further, the semi-finished aluminum-plastic film after the transition curing treatment is subjected to constant-speed curing treatment for 5s to 8s.
[0077] In one embodiment, the semi-finished aluminum-plastic film after constant-speed curing is subjected to reduced-speed curing at a temperature of 80° C. to 100° C. Further, the semi-finished aluminum-plastic film after constant-speed curing is subjected to reduced-speed curing for 5s to 8s.
[0078] It can be understood that the transition curing treatment of the semi-finished aluminum-plastic film, on the one hand, preheats the curing to improve the curing effect of the anti-corrosion slippery layer, and on the other hand, the setting temperatures are 55°C to 75°C and 70°C to 90°C, respectively, and the processing time is 5s to 8s, which better reduces the rapid drying of the solvent on the surface of the anti-corrosion slippery layer and affects the surface flatness, and better ensures the overall rapid and effective release and volatilization of the solvent in the anti-corrosion slippery layer, and further makes the constant speed curing treatment at a temperature of 100°C to 120°C for 5s to 8s, combined with the reduced speed curing treatment at a temperature of 80°C to 100°C, effectively ensuring the full curing of the anti-corrosion slippery layer, and further while reducing the impact on the surface flatness of the anti-corrosion slippery layer, promotes the rapid and effective release and volatilization of the solvent inside the anti-corrosion slippery layer.
[0079] In one embodiment, the thickness of the anti-corrosion slippery layer is 0.1 μm to 0.5 μm.
[0080] In one embodiment, the pre-treated aluminum-plastic film is treated with a slippery coating, wherein the slippery coating comprises the following components by weight: 70 to 80 parts of ethylene bisstearamide; 20 to 30 parts of chlorinated polypropylene. The formed slippery layer and the CPP material layer have good adsorption, thermal stability and chemical stability, high mechanical strength, are not easy to fall off, and have a good slippery effect.
[0081] It should be noted that the materials of the anti-corrosion and lubricating layers are independently selected and do not need to be limited to be the same.
[0082] It can be understood that the formation of a slippery layer on the surface of the CPP layer can reduce the bonding strength of the CPP layer under heat sealing by controlling the amount of the substance having a slippery effect. However, in fact, no matter how the amount of the substance having a slippery effect is controlled, the setting of the slippery layer will still cause the bonding strength of the CPP layer under heat sealing, thereby reducing the sealing stability of the aluminum-plastic film package. Therefore, in order to better ensure the sealing stability of the aluminum-plastic film package, in one embodiment, a slippery coating is used to perform a slippery treatment on the pre-treated aluminum-plastic film, specifically: the slippery coating is electrostatically spun on the surface of the CPP layer of the semi-finished aluminum-plastic film. Further, the slippery coating is placed in an electrostatic spinning machine, the CPP layer of the semi-finished aluminum-plastic film is used as a receiving substrate, and the electrostatic spinning parameters are set to electrostatically spin the slippery coating. Furthermore, the parameters for setting the electrospinning include: setting the voltage to 8 kV to 20 kV; the distance between the nozzle of the electrospinning machine and the CPP layer to 10 cm to 20 cm; the extrusion speed of the slippery coating to 0.008 mL / min to 0.3 mL / min; and the temperature to 150° C. to 160° C.
[0083] It can be understood that electrospinning makes the slippery layer have more pores, and more pores combined with the thickness of the slippery layer of 0.1μm to 0.5μm allow the slippery layer to penetrate the slippery layer and bond together during the heat sealing process, thereby better ensuring the sealing stability of the aluminum-plastic film package.
[0084] It should be noted that the use of solvents causes gaps to form on the slippery coating, which will affect the slippery effect of the slippery coating. In addition, since the structure of the CPP layer is easily destroyed after heat treatment, the slippery coating in this application does not use solvents and adopts melt electrospinning. There is no need to subsequently heat treat and dry the solvent, which better ensures the stability of the CPP layer and the slippery effect of the slippery coating.
[0085] In one embodiment, the viscosity of the slippery coating is 1 Pa·s to 5 Pa·s.
[0086] In one embodiment, the porosity of the smooth layer is 40% to 50%. Further, the spinning of the smooth layer is arranged horizontally and vertically. It can be understood that the presence of the pores of the smooth layer reduces the contact area during stamping, further reduces the friction strength, and the spinning of the smooth layer is arranged horizontally and vertically, and the intersection of the spinning arranged horizontally and vertically is in the stamping groove. Further, the intersection of the spinning is in the center of the stamping groove with a radius of 0.5cm to 1.0cm. In another embodiment, the spinning of the smooth layer is radial, and the center of the radial spinning is in the stamping groove. Further, the center of the radial spinning is located at the center of the stamping groove, which further better ensures that the smooth effect can be improved in the horizontal and vertical directions during stamping, and further better ensures the smooth effect during stamping, and then better ensures the deep punching performance and outer surface corrosion resistance of the aluminum-plastic film, and then better meets the needs of users.
[0087] In one embodiment, the method for preparing the slippery coating comprises the following steps:
[0088] The chlorinated polypropylene and ethylene bis stearamide are mixed in a solid state to obtain a mixture;
[0089] Furthermore, the mixed material is subjected to a melt mixing process.
[0090] In one embodiment, the mixed material is melt-mixed, specifically, the mixed material is melt-mixed using a screw extruder. Further, the temperature of the melt-mixing is 150° C. to 160° C. In one embodiment, the thickness of the slippery layer is 0.1 μm to 0.5 μm.
[0091] In one of the embodiments, the method for preparing an aluminum-plastic film with a smooth surface and corrosion resistance is carried out in an environment where the cleanliness requirement is above Class 10,000, the number of dust particles greater than or equal to 0.5 cannot exceed 32,000, and in particular, the number of dust particles greater than or equal to 0.5 in the oven must not exceed 1,000, which effectively reduces the impact of the formation of the anti-corrosion slippery layer and the slippery layer.
[0092] The present application also provides an aluminum-plastic film with a smooth surface and corrosion resistance. The above-mentioned aluminum-plastic film with a smooth surface and corrosion resistance is prepared by the method for preparing an aluminum-plastic film with a smooth surface and corrosion resistance in any of the above-mentioned embodiments. Further, the method for preparing an aluminum-plastic film with a smooth surface and corrosion resistance comprises the following steps: performing a surface passivation treatment operation on an aluminum foil to obtain a passivated aluminum foil; performing a layer composite operation on the passivated aluminum foil to composite the matte surface of the passivated aluminum foil with the nylon material layer, and the bright surface of the passivated aluminum foil with the CPP layer to obtain a composite aluminum foil; performing a aging operation on the composite aluminum foil to obtain a semi-finished aluminum-plastic film; performing a smooth and anti-corrosion treatment on the semi-finished aluminum-plastic film to form an anti-corrosion and smooth layer on the surface of the nylon material layer of the semi-finished aluminum-plastic film; performing a smooth treatment on the pretreated aluminum-plastic film to form a smooth layer on the surface of the CPP layer of the semi-finished aluminum-plastic film.
[0093] The aluminum-plastic film with a smooth surface and corrosion resistance can better ensure the heat-sealing stability and has a good smooth effect, thus better ensuring the safety of the battery.
[0094] Compared with the prior art, the present invention has at least the following advantages:
[0095] The method for preparing the aluminum-plastic film with a smooth and corrosion-resistant surface comprises the following steps: firstly, performing a surface passivation treatment operation on the aluminum foil, and then performing a layer composite operation on the passivated aluminum foil, so as to better realize the composite of the nylon material layer and the CPP layer on the passivated aluminum foil; then performing a aging operation on the composite aluminum foil, so as to better ensure the composite strength of the nylon material layer and the CPP layer on the passivated aluminum foil; finally, performing a smooth and corrosion-resistant treatment on the semi-finished aluminum-plastic film, and performing a smooth treatment on the pre-treated aluminum-plastic film, so as to directly reduce the stamping friction; and the anti-corrosion smooth layer is used to compensate for and buffer the stamping friction, so that the smooth performance of the smooth layer can better ensure the deep punching performance and the outer surface corrosion resistance of the aluminum-plastic film without affecting the packaging bonding strength, thereby better meeting the needs of users, avoiding the problem that the smooth effect of the smooth layer formed on the surface of the CPP layer of the aluminum-plastic film is too strong, that is, avoiding the problem that the surface of the CPP layer of the aluminum-plastic film is too smooth, thereby affecting the packaging bonding strength of the aluminum-plastic film, and better ensuring the use safety of the battery.
[0096] Some specific examples are listed below, and if % is mentioned, it means percentage by weight. It should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial sources unless otherwise specified.
[0097] Example 1
[0098] The aluminum foil was immersed in a 100 ml / L RC-650 trivalent chromium aluminum passivator aqueous solution for passivation at a temperature of 39°C and a pH of 3 for 5 min, and then air-dried;
[0099] The matte surface of the aluminum foil is bonded with the nylon material layer using a polyurethane adhesive, and the bright surface of the aluminum foil is bonded with the CPP layer using a maleic anhydride-modified polypropylene adhesive, and then placed at room temperature for 1 hour to allow the glue to fully penetrate into each film layer; then placed at a temperature of 40°C for 24 hours to allow the glue to flow better; finally, placed at a temperature of 50°C for 168 hours to allow the glue to fully solidify to obtain an aluminum-plastic film, and then a corona machine with a power of 0.5Kw is used to corona the nylon layer of the aluminum-plastic film and set it aside;
[0100] The organosilicon-modified acrylate and the chemical corrosion-resistant fluoropolymer were stirred and mixed at a stirring speed of 200 r / min for 10 min, then the solvent was added and continued to be stirred at a stirring speed of 200 r / min for 15 min, then the epoxy curing agent was added and continued to be stirred at a stirring speed of 300 r / min for 8 min, then the isocyanate curing agent was added and continued to be stirred at a stirring speed of 300 r / min for 12 min, to obtain an anti-corrosion and smooth coating;
[0101] The anti-corrosion and lubricating coating is applied to the nylon layer of the aluminum-plastic film, and then cured, specifically: the temperature is 55°C, stay for 8s; the temperature is 70°C, stay for 8s; the temperature is 100°C, stay for 8s; the temperature is 80°C, stay for 8s, and a 0.1 μm thick anti-corrosion and lubricating layer is formed on the nylon layer of the aluminum-plastic film;
[0102] Chlorinated polypropylene and ethylene bis stearamide were stirred and mixed at a stirring speed of 200 r / min for 10 min, and then added into a spiral mixer for mixing and extrusion at a temperature of 150°C and kept at a constant temperature to obtain a smooth coating;
[0103] The slippery coating is spun on the CPP layer of the aluminum-plastic film through an electrospinning machine. The parameters of the electrospinning are set as follows: the voltage is set to 8 kV; the distance between the nozzle of the electrospinning machine and the CPP layer is 10 cm; the extrusion speed of the slippery coating is 0.008 mL / min; the temperature is 150°C, and after cooling, a slippery layer with a thickness of 0.1 μm is formed on the CPP layer of the aluminum-plastic film, and the porosity of the slippery layer is 40%.
[0104] Example 2
[0105] The matte surface of the aluminum foil is bonded with the nylon material layer using a polyurethane adhesive, and the bright surface of the aluminum foil is bonded with the CPP layer using a maleic anhydride-modified polypropylene adhesive, and then placed at room temperature for 5 hours to allow the glue to fully penetrate into each film layer; then placed at a temperature of 42°C for 18 hours to allow the glue to flow better; finally, placed at a temperature of 60°C for 130 hours to allow the glue to fully solidify to obtain an aluminum-plastic film, and then a corona machine with a power of 0.8Kw is used to corona the nylon layer of the aluminum-plastic film and set it aside;
[0106] The remaining steps are the same as those in Example 1.
[0107] Example 3
[0108] The matte surface of the aluminum foil is bonded with the nylon material layer using a polyurethane adhesive, and the bright surface of the aluminum foil is bonded with the CPP layer using a maleic anhydride-modified polypropylene adhesive, and then placed at room temperature for 10 hours to allow the glue to fully penetrate into each film layer; then placed at a temperature of 45°C for 12 hours to 24 hours to allow the glue to flow better; finally, placed at a temperature of 70°C for 96 hours to allow the glue to fully solidify to obtain an aluminum-plastic film, and then a corona machine with a power of 1.5Kw is used to corona the nylon layer of the aluminum-plastic film and set it aside;
[0109] The remaining steps are the same as those in Example 1.
[0110] Example 4
[0111] The organosilicon-modified acrylate and the chemical corrosion-resistant fluoropolymer were stirred and mixed at a stirring speed of 250 r / min for 10 min, then the solvent was added and continued to be stirred at a stirring speed of 250 r / min for 12 min, then the epoxy curing agent was added and continued to be stirred at a stirring speed of 350 r / min for 6 min, then the isocyanate curing agent was added and continued to be stirred at a stirring speed of 350 r / min for 10 min, to obtain an anti-corrosion and smooth coating;
[0112] The remaining steps are the same as those in Example 2.
[0113] Example 5
[0114] The organosilicon-modified acrylate and the chemical corrosion-resistant fluoropolymer were stirred and mixed at a stirring speed of 300 r / min for 10 min, then the solvent was added and continued to be stirred at a stirring speed of 300 r / min for 8 min, then the epoxy curing agent was added and continued to be stirred at a stirring speed of 350 r / min for 4 min, then the isocyanate curing agent was added and continued to be stirred at a stirring speed of 350 r / min for 8 min, to obtain an anti-corrosion and smooth coating;
[0115] The remaining steps are the same as those in Example 2.
[0116] Example 6
[0117] The anti-corrosion and lubricating coating is applied to the nylon layer of the aluminum-plastic film, and then cured, specifically: the temperature is 60°C, stay for 7s; the temperature is 80°C, stay for 7s; the temperature is 110°C, stay for 7s; the temperature is 90°C, stay for 7s, and the anti-corrosion and lubricating layer with a thickness of 0.1 μm is formed on the nylon layer of the aluminum-plastic film;
[0118] The remaining steps are the same as those in Example 4.
[0119] Example 7
[0120] The anti-corrosion and lubricating coating is applied to the nylon layer of the aluminum-plastic film, and then cured, specifically: the temperature is 75°C, stay for 5s; the temperature is 90°C, stay for 5s; the temperature is 100°C, stay for 5s; the temperature is 80°C, stay for 5s, and an anti-corrosion and lubricating layer with a thickness of 0.1 μm is formed on the nylon layer of the aluminum-plastic film;
[0121] The remaining steps are the same as those in Example 4.
[0122] Example 8
[0123] A 0.3 μm thick anti-corrosion and smooth layer is formed on the nylon layer of the aluminum-plastic film;
[0124] The remaining steps are the same as those in Example 6.
[0125] Example 9
[0126] A 0.5 μm thick anti-corrosion and smooth layer is formed on the nylon layer of the aluminum-plastic film;
[0127] The remaining steps are the same as those in Example 6.
[0128] Example 10
[0129] Chlorinated polypropylene and ethylene bis stearamide were stirred and mixed at a stirring speed of 250 r / min for 10 min, and then added into a spiral mixer for mixing and extrusion at a temperature of 155°C and kept at a constant temperature to obtain a smooth coating;
[0130] The remaining steps are the same as those in Example 8.
[0131] Embodiment 11
[0132] Chlorinated polypropylene and ethylene bis stearamide were stirred and mixed at a stirring speed of 300 r / min for 10 min, and then added into a spiral mixer for mixing and extrusion at a temperature of 160°C and kept at a constant temperature to obtain a smooth coating;
[0133] The remaining steps are the same as those in Example 8.
[0134] Example 12
[0135] The slippery coating is spun on the CPP layer of the aluminum-plastic film through an electrospinning machine. The parameters of the electrospinning are set as follows: the voltage is set to 10 kV; the distance between the nozzle of the electrospinning machine and the CPP layer is 15 cm; the extrusion speed of the slippery coating is 0.05 mL / min; the temperature is 150°C, and after cooling, a slippery layer with a thickness of 0.1 μm is formed on the CPP layer of the aluminum-plastic film, and the porosity of the slippery layer is 40%.
[0136] The remaining steps are the same as in Example 10.
[0137] Example 13
[0138] The slippery coating is spun on the CPP layer of the aluminum-plastic film through an electrospinning machine, and the parameters of the electrospinning are set as follows: the voltage is set to 15 kV; the distance between the nozzle of the electrospinning machine and the CPP layer is 18 cm; the extrusion speed of the slippery coating is 0.2 mL / min; the temperature is 155° C., and after cooling, a slippery layer with a thickness of 0.1 μm is formed on the CPP layer of the aluminum-plastic film, and the porosity of the slippery layer is 40%;
[0139] The remaining steps are the same as in Example 10.
[0140] Embodiment 14
[0141] The slippery coating is spun on the CPP layer of the aluminum-plastic film through an electrospinning machine, and the parameters of the electrospinning are set as follows: the voltage is set to 20 kV; the distance between the nozzle of the electrospinning machine and the CPP layer is 20 cm; the extrusion speed of the slippery coating is 0.3 mL / min; the temperature is 160° C., and after cooling, a slippery layer with a thickness of 0.1 μm is formed on the CPP layer of the aluminum-plastic film, and the porosity of the slippery layer is 40%;
[0142] The remaining steps are the same as in Example 10.
[0143] Embodiment 15
[0144] A slippery layer with a thickness of 0.3 μm is formed on the CPP layer of the aluminum-plastic film, and the porosity of the slippery layer is 45%;
[0145] The remaining steps are the same as Example 13.
[0146] Example 16
[0147] A slippery layer with a thickness of 0.5 μm is formed on the CPP layer of the aluminum-plastic film, and the porosity of the slippery layer is 50%;
[0148] The remaining steps are the same as Example 13.
[0149] Embodiment 17
[0150] The aluminum foil was immersed in a 100 ml / L RC-650 trivalent chromium aluminum passivator aqueous solution for passivation at a temperature of 39°C and a pH of 3 for 5 min, and then air-dried;
[0151] The matte surface of the aluminum foil is bonded with a polyurethane adhesive to bond the nylon material layer, and the bright surface of the aluminum foil is bonded with a maleic anhydride-modified polypropylene adhesive to bond the CPP layer. The composite is then placed at room temperature for 5 hours to allow the glue to fully penetrate into each film layer; then, it is placed at a temperature of 42°C for 18 hours to allow the glue to flow better; finally, it is placed at a temperature of 60°C for 130 hours to allow the glue to fully cure to obtain an aluminum-plastic film.
[0152] Embodiment 18
[0153] The aluminum foil was immersed in a 100 ml / L RC-650 trivalent chromium aluminum passivator aqueous solution for passivation at a temperature of 39°C and a pH of 3 for 5 min, and then air-dried;
[0154] The matte surface of the aluminum foil is bonded with the nylon material layer using a polyurethane adhesive, and the bright surface of the aluminum foil is bonded with the CPP layer using a maleic anhydride-modified polypropylene adhesive, and then placed at room temperature for 5 hours to allow the glue to fully penetrate into each film layer; then placed at a temperature of 42°C for 18 hours to allow the glue to flow better; finally, placed at a temperature of 60°C for 130 hours to allow the glue to fully solidify to obtain an aluminum-plastic film, and then a corona machine with a power of 0.8Kw is used to corona the nylon layer of the aluminum-plastic film and set it aside;
[0155] The organosilicon-modified acrylate and the chemical corrosion-resistant fluoropolymer were stirred and mixed at a stirring speed of 250 r / min for 10 min, then the solvent was added and continued to be stirred at a stirring speed of 250 r / min for 12 min, then the epoxy curing agent was added and continued to be stirred at a stirring speed of 350 r / min for 6 min, then the isocyanate curing agent was added and continued to be stirred at a stirring speed of 350 r / min for 10 min, to obtain an anti-corrosion and smooth coating;
[0156] The anti-corrosion and lubricating coating is applied to the nylon layer of the aluminum-plastic film, and then cured, specifically: temperature at 60°C, stay for 7s; temperature at 80°C, stay for 7s; temperature at 110°C, stay for 7s; temperature at 90°C, stay for 7s, to form an anti-corrosion and lubricating layer with a thickness of 0.3μm on the nylon layer of the aluminum-plastic film.
[0157] Embodiment 19
[0158] The aluminum foil was immersed in a 100 ml / L RC-650 trivalent chromium aluminum passivator aqueous solution for passivation at a temperature of 39°C and a pH of 3 for 5 min, and then air-dried;
[0159] The matte surface of the aluminum foil is bonded with the nylon material layer using a polyurethane adhesive, and the bright surface of the aluminum foil is bonded with the CPP layer using a maleic anhydride-modified polypropylene adhesive, and then placed at room temperature for 5 hours to allow the glue to fully penetrate into each film layer; then placed at a temperature of 42°C for 18 hours to allow the glue to flow better; finally, placed at a temperature of 60°C for 130 hours to allow the glue to fully solidify to obtain an aluminum-plastic film, and then a corona machine with a power of 0.8Kw is used to corona the nylon layer of the aluminum-plastic film and set it aside;
[0160] The organosilicon-modified acrylate and the chemical corrosion-resistant fluoropolymer were stirred and mixed at a stirring speed of 250 r / min for 10 min, then the solvent was added and continued to be stirred at a stirring speed of 250 r / min for 12 min, then the epoxy curing agent and the isocyanate curing agent were added and continued to be stirred at a stirring speed of 350 r / min for 16 min, to obtain an anti-corrosion and smooth coating;
[0161] The anti-corrosion and lubricating coating is applied to the nylon layer of the aluminum-plastic film, and then cured, specifically: temperature at 60°C, stay for 7s; temperature at 80°C, stay for 7s; temperature at 110°C, stay for 7s; temperature at 90°C, stay for 7s, to form an anti-corrosion and lubricating layer with a thickness of 0.3μm on the nylon layer of the aluminum-plastic film.
[0162] Embodiment 20
[0163] The aluminum foil was immersed in a 100 ml / L RC-650 trivalent chromium aluminum passivator aqueous solution for passivation at a temperature of 39°C and a pH of 3 for 5 min, and then air-dried;
[0164] The matte surface of the aluminum foil is bonded with the nylon material layer using a polyurethane adhesive, and the bright surface of the aluminum foil is bonded with the CPP layer using a maleic anhydride-modified polypropylene adhesive, and then placed at room temperature for 5 hours to allow the glue to fully penetrate into each film layer; then placed at a temperature of 42°C for 18 hours to allow the glue to flow better; finally, placed at a temperature of 60°C for 130 hours to allow the glue to fully solidify to obtain an aluminum-plastic film, and then a corona machine with a power of 0.8Kw is used to corona the nylon layer of the aluminum-plastic film and set it aside;
[0165] The organosilicon-modified acrylate and the chemical corrosion-resistant fluoropolymer were stirred and mixed at a stirring speed of 250 r / min for 10 min, then the solvent was added and continued to be stirred at a stirring speed of 250 r / min for 12 min, then the epoxy curing agent was added and continued to be stirred at a stirring speed of 350 r / min for 6 min, then the isocyanate curing agent was added and continued to be stirred at a stirring speed of 350 r / min for 10 min, to obtain an anti-corrosion and smooth coating;
[0166] The anti-corrosion and lubricating coating is applied to the nylon layer of the aluminum-plastic film, and then cured, specifically: temperature is 50°C, stay for 7s; temperature is 60°C, stay for 7s; temperature is 90°C, stay for 7s; temperature is 70°C, stay for 7s, to form an anti-corrosion and lubricating layer with a thickness of 0.3μm on the nylon layer of the aluminum-plastic film.
[0167] Embodiment 21
[0168] The aluminum foil was immersed in a 100 ml / L RC-650 trivalent chromium aluminum passivator aqueous solution for passivation at a temperature of 39°C and a pH of 3 for 5 min, and then air-dried;
[0169] The matte surface of the aluminum foil is bonded with the nylon material layer using a polyurethane adhesive, and the bright surface of the aluminum foil is bonded with the CPP layer using a maleic anhydride-modified polypropylene adhesive, and then placed at room temperature for 5 hours to allow the glue to fully penetrate into each film layer; then placed at a temperature of 42°C for 18 hours to allow the glue to flow better; finally, placed at a temperature of 60°C for 130 hours to allow the glue to fully solidify to obtain an aluminum-plastic film, and then a corona machine with a power of 0.8Kw is used to corona the nylon layer of the aluminum-plastic film and set it aside;
[0170] The organosilicon-modified acrylate and the chemical corrosion-resistant fluoropolymer were stirred and mixed at a stirring speed of 250 r / min for 10 min, then the solvent was added and continued to be stirred at a stirring speed of 250 r / min for 12 min, then the epoxy curing agent was added and continued to be stirred at a stirring speed of 350 r / min for 6 min, then the isocyanate curing agent was added and continued to be stirred at a stirring speed of 350 r / min for 10 min, to obtain an anti-corrosion and smooth coating;
[0171] The anti-corrosion and lubricating coating is applied to the nylon layer of the aluminum-plastic film, and then cured, specifically: temperature is 80°C, stay for 7s; temperature is 95°C, stay for 7s; temperature is 130°C, stay for 7s; temperature is 110°C, stay for 7s, to form an anti-corrosion and lubricating layer with a thickness of 0.3μm on the nylon layer of the aluminum-plastic film.
[0172] Embodiment 22
[0173] The lubricating coating is applied on the CPP layer of the aluminum-plastic film, and after cooling, a lubricating layer with a thickness of 0.3 μm is formed on the CPP layer of the aluminum-plastic film;
[0174] The remaining steps are the same as in Example 10.
[0175] The above operations are carried out in an environment where the cleanliness requirement is above Class 10,000, the number of dust particles greater than or equal to 0.5 shall not exceed 32,000, and especially the number of dust particles greater than or equal to 0.5 in the oven shall not exceed 1,000.
[0176] The specific substances and specific amounts of the anticorrosive and slippery coatings and slippery coatings in Examples 1 to 8 are shown in Table 1:
[0177] Table 1: Details of the substances and amounts of the anticorrosive and slippery coatings and slippery coatings in Examples 1 to 22
[0178]
[0179]
[0180] It should be noted that the operating steps of Examples 15-1 to 15-8 are the same as those of Example 15, the only difference being that the substances used and the corresponding amounts are not exactly the same.
[0181] The following tests and records are made on the smoothness effects of the products prepared in each embodiment.
[0182] 1. The aluminum-plastic film in the embodiment has a size of 113um, a width of 120mm and a length of 300m. The roll sample is placed in a constant temperature environment of 35°C (wherein the ambient temperature measured at 0h is 25°C). The dynamic friction coefficient of the product is tracked every week for 6 consecutive weeks. The results are shown in Tables 2-3:
[0183] Table 2: Dynamic friction coefficient of nylon layer of products prepared in various embodiments
[0184]
[0185]
[0186] Table 3: CPP layer dynamic friction coefficient of the products prepared in each embodiment
[0187]
[0188]
[0189] 2. The size of the aluminum-plastic film in each embodiment is a roll sample of 113um, 120mm wide and 300m long. A 18350 forming die is used, and 100 pieces are continuously punched. The height of the punched cylinder is the punching depth. The punching depth is controlled to be 8.5mm. The number of repetitions of each embodiment is 1000. The defective rate of the aluminum-plastic film in each embodiment is recorded. The recorded results are shown in Table 4. The average value is taken below:
[0190] Table 4: Deep drawing performance of products prepared in various embodiments
[0191]
[0192]
[0193] 3. In each embodiment, 5 pieces of long strip samples with a length greater than 100 mm and a width of (15±0.1) mm were cut from the aluminum-plastic film in the horizontal and vertical directions, folded in half and heat-sealed (hard seal 190 / 190°C, 0.4 MPa, 3 sec), and tested using a tensile testing machine. The initial distance between the clamps was (50±5) mm, and the test was performed at a speed of (300±20) mm / min. The maximum force value was recorded. Reference standard: QB / T2358-1998.
[0194] Table 5: Heat seal strength of CPP layer of products prepared in various examples
[0195]
[0196]
[0197]
[0198] It can be seen from Tables 2 to 5 that the slippery layer formed by electrospinning the slippery coating on the CPP layer in the present application has a good slippery effect and will not affect the heat sealing strength of the aluminum-plastic film. In particular, please refer to Figure 2, is the aluminum-plastic film prepared in Example 15-6, a is the slippery layer on the surface of the CPP layer, and b is the anti-corrosion slippery layer on the surface of the nylon material layer. The aluminum-plastic film of Example 15-6 has a better slippery effect and will not affect the heat sealing strength of the aluminum-plastic film.
[0199] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a smooth and corrosion-resistant aluminum-plastic film, characterized in that: The following steps are involved: Performing a surface passivation treatment operation on the aluminum foil to obtain a passivated aluminum foil; Performing a layer compounding operation on the passivated aluminum foil so that the matte surface of the passivated aluminum foil is compounded with the nylon material layer, and the bright surface of the passivated aluminum foil is compounded with the CPP layer, to obtain a composite aluminum foil; Performing a aging operation on the composite aluminum foil to obtain a semi-finished aluminum-plastic film; Performing a lubrication and anti-corrosion treatment on the semi-finished aluminum-plastic film so as to form an anti-corrosion and lubrication layer on the surface of the nylon material layer of the semi-finished aluminum-plastic film; The pre-treated aluminum-plastic film is subjected to a slippery treatment so that a slippery layer is formed on the surface of the CPP layer of the semi-finished aluminum-plastic film.
2. The method for preparing the aluminum-plastic film having a smooth surface and corrosion resistance according to claim 1, characterized in that: The semi-finished aluminum-plastic film is treated with anti-corrosion and anti-slip coating; The anti-corrosion and slippery coating comprises the following components in parts by weight: The main agent at least includes organosilicon-modified acrylate and chemical corrosion-resistant fluoropolymer.
3. The method for preparing the aluminum-plastic film having a smooth surface and corrosion resistance according to claim 2, characterized in that: The chemical corrosion resistant fluoropolymer is at least one of polytetrafluoroethylene (PTFE), fluorinated ethylene propylene (FEVAC), fluorinated alkyl acrylate (FMA) and fluorinated ethylene propylene copolymer (FEP).
4. The method for preparing the aluminum-plastic film having a smooth surface and corrosion resistance according to claim 2, characterized in that: The mass ratio of the organosilicon-modified acrylate to the chemical corrosion-resistant fluoropolymer is (0.5-2):
1.
5. The method for preparing the aluminum-plastic film having a smooth surface and corrosion resistance according to claim 2, characterized in that: The mass percentage concentration of the organosilicon-modified acrylate in the anti-corrosion and slippery coating is 15% to 30%.
6. The method for preparing the aluminum-plastic film having a smooth surface and corrosion resistance according to claim 2, characterized in that: The preparation method of the anticorrosive and slippery coating comprises the following steps: The silicone-modified acrylate and the chemical corrosion-resistant fluoropolymer are mixed to obtain the main agent; Adding a solvent to the main agent to perform a first stirring and mixing operation to obtain a first mixed solution; Adding the epoxy curing agent to the first mixed liquid to perform a second stirring and mixing operation to obtain a second mixed liquid; The isocyanate curing agent is added to the second mixed liquid to perform a third stirring and mixing operation to obtain the anti-corrosion and slippery coating.
7. The method for preparing the aluminum-plastic film having a smooth surface and corrosion resistance according to claim 6, characterized in that: Adding the epoxy curing agent to the first mixed solution for a second stirring and mixing operation, the stirring speed is 350±50r / min, and the stirring time is 4min to 8min; and / or, The isocyanate curing agent is added to the second mixed liquid to perform a third stirring and mixing operation, with a stirring speed of 350±50 r / min and a stirring time of 8 min to 12 min.
8. The method for preparing the aluminum-plastic film having a smooth surface and corrosion resistance according to claim 1, characterized in that: Before the step of performing a lubricity treatment on the pretreated aluminum-plastic film and after the step of performing a lubricity and anti-corrosion treatment on the semi-finished aluminum-plastic film, the method for preparing the aluminum-plastic film with a lubricity and corrosion resistance further comprises the following steps: The semi-finished aluminum-plastic film after the lubrication and anti-corrosion treatment is subjected to a gradient curing operation, so that an anti-corrosion and lubrication layer is formed on the surface of the nylon material layer of the semi-finished aluminum-plastic film.
9. The method for preparing the aluminum-plastic film having a smooth surface and corrosion resistance according to claim 1, characterized in that: Before the step of performing a smooth and anti-corrosion treatment on the semi-finished aluminum-plastic film and after the step of performing a aging operation on the composite aluminum foil, the method for preparing the aluminum-plastic film with a smooth surface and anti-corrosion further comprises the following steps: The nylon material layer of the semi-finished aluminum-plastic film is subjected to corona treatment.
10. A smooth and corrosion-resistant aluminum-plastic film, characterized in that: The aluminum-plastic film is prepared by the method for preparing the aluminum-plastic film with smooth surface and corrosion resistance as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Corrosion-resistant aluminum-plastic composite film and preparation method thereof
CN116001399A
Corrosion-resistant coating as well as preparation method and application thereof
CN116715999A
Composite packaging high-corrosion-resistant barrier aluminum-plastic film for lithium battery
CN104966798A
Preparation method for aluminum-plastic composite film
CN108481863A
Smooth coating liquid for aluminum plastic thin film and coating process thereof
CN110760259A